2023
DOI: 10.3389/fpubh.2023.1163492
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Spanish nurses in the rollout of nurse prescribing: a qualitative study

Olga Canet-Vélez,
Gloria Jodar-Solà,
Jaume Martín-Royo
et al.

Abstract: IntroductionNurse prescribing has legal recognition in Spain, after a long regulatory process, with confusing, changing legislation that does not fully coincide with the reality of nurses' practice. There is currently no research available on how nurses have experienced the rollout of nurse prescribing. The objective of this study is to describe the experiences of nurses in the rollout of nurse prescribing in the province of Barcelona, Spain.MethodA descriptive qualitative study with intentional sampling was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Nurse prescriptions for medication and health products have increased around the world, but the heterogeneity of legal and organizational frameworks in different countries makes the analysis of this practice complex [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse prescriptions for medication and health products have increased around the world, but the heterogeneity of legal and organizational frameworks in different countries makes the analysis of this practice complex [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ruiz et al has shown that NP practice is associated with higher quality care for people requiring medical services, more efficient use of time and resources, and better collaboration among healthcare professionals [ 3 ]. NP is described as a process that increases nurses’ decision-making and leadership capabilities, promoting greater empowerment in the workplace, with expanded recognition of their roles and competencies, becoming references for patients and colleagues [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uniform mandated regulations of permitted prescribing by health care providers, coupled with specialized formularies for various practitioners, including nurses, may improve interprofessional communication, cooperation, and organized distribution of responsibilities and accountability in delivery of PC in psychiatric mental health settings (Canet-Vélez et al, 2023; Courtenay, 2010; Skingsley et al, 2006; While & Biggs, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This has been evidenced by reduced readmission rates among patients who are cared for nurses with expanded roles in PC in Europe (Graham-Clarke et al, 2019). Structured expansion of the PC role may assist in reducing caring responsibilities for other members of the interprofessional team (McCurdy et al, 2020; Nuttall, 2018) while providing a safety framework for the prescribing nurse (Canet-Vélez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Experiences of Spanish nurses in the rollout of nurse prescribing were explored [ [8] , [9] , [10] ], which can provide references for us. Nursing organizations certify and monitor nurse prescribing within the policy framework.…”
Section: Introductionmentioning
confidence: 99%